Providensia Allah bagi Kebahagiaan Rumah Tangga Kristen - Nurlela Syafrian Oematan (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The Christian home is like a vast ocean to be crossed. On the journey across the vast ocean, sometimes you will experience calm, but often it will be turbulent, through typhoons, filled with rocks and icebergs. However, many arks of Christian households are sunk or divorced because of hitting rocks or complicated problems, and innocent children remain as victims. This happens because of the lack of preparation that is carried out before entering the household or also because of the lack of preparation that is carried out before entering the household or also because of a lack of vigilance in living a household life, it is necessary to provide God's providence in the household. Therefore, the author uses an inductive method in the form of literature studies as the theological basis for God's providence in marriage for the happiness of Christian households.AbstrakRumah tangga Kristen bagaikan samudra luas yang harus ditempuh. Dalam perjalanan mengarungi samudra luas itu kadang-kadang mengalami ketenangan, namun seringkali bergelora, menempuh topan, dipenuhi oleh batu-batu karang serta gunung es. Namun banyak sekali bahtera rumah tangga Kristen menjadi karam atau bercerai karena membentur batu karang atau masalah yang pelik, dan tinggallah anak-anak yang tidak bersalah sebagai korbannya. Hal ini terjadi oleh karena kurangnya persiapan yang diadakan sebelum mengarungi rumah tangga atau juga karena kurangnya persiapan yang diadakan sebelum mengarungi rumah tangga atau juga karena kurang adanya kewaspadaan dalam menjalani kehidupan rumah tangga, maka perlu providensia Allah dalam berumah tangga. Oleh sebab itu penulis menggunakan metode induktif berupa studi literature sebagai landasan teologi terhadap providensia Allah dalam berumah tangga bagi kebahagiaan rumah tangga Kristen.